Evaluasi pemeliharaan taman pada kawasan Bali tropic resort and spa Kabupaten Badung - Istacahyani, Ida Ayu Modasih; Semarajaya, Cokorda Gede Alit; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap, 2018)
Evaluation of garden maintenance in Bali tropic resort and spa area of Badung Regency. Maintenance of the park in the area of Bali Tropic Resort and Spa has been gone on since 27 years, so it is interesting to know the efforts that have been done and how the visitors response to the maintenance of the park in the area resort. The purpose of this research is to identify and to evaluate system the maintenance of the park at the Bali Tropic Resort and Spa area. The research method used is survey method. The data collected in this research are primary data and secondary data. Data collection techniques used are observation technique, interview technique, literature study and questionnaire. Interviews were conducted with related parties and questionnaires distributed to 30 respondents with the criteria of using English well. Maintenance system which implemented is a maintenance unit and specialized maintenance system. The results of the evaluation of the maintenance of the park has been well viewed from the cleanliness of the park, the park security, the beauty of the park, cleanliness of fish, cleanliness of planter box, and pavement cleanliness. Suggestions given are written standard of maintenance, maintenance schedule, monitoring card, a reward system in the form of charter and achievement allowance for garden staff to improve work motivation and work discipline so it also can improve the effectiveness and efficiency of work and training that can increase knowledge and skills in maintenance activities for the employee.